2009
DOI: 10.1093/ejechocard/jep013
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of right ventricular function by real-time three-dimensional echocardiography improves accuracy and decreases interobserver variability compared with conventional two-dimensional views

Abstract: RT3DE provides improved accuracy of RV function assessment and decreases interobserver variability when compared with 2D views.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…24 Indeed, the normal RV is a crescentshaped structure wrapped around the LV and is incompletely visualized in any single 2DE view. 31,32 A study performed on healthy adult subjects showed that 3DE was better correlated to magnetic resonance imaging (MRI) than 2DE because 3DE was more able to include important volumes. Although several 2DE quantitative methods, which are based on geometric assumptions, were described, [24][25][26] direct calculation of RV volumes remains problematic.…”
Section: Discussionmentioning
confidence: 99%
“…24 Indeed, the normal RV is a crescentshaped structure wrapped around the LV and is incompletely visualized in any single 2DE view. 31,32 A study performed on healthy adult subjects showed that 3DE was better correlated to magnetic resonance imaging (MRI) than 2DE because 3DE was more able to include important volumes. Although several 2DE quantitative methods, which are based on geometric assumptions, were described, [24][25][26] direct calculation of RV volumes remains problematic.…”
Section: Discussionmentioning
confidence: 99%
“…Real time three‐dimensional echocardiography (RT3DE) is a newly developed echocardiographic technique to display the complex three‐dimensional anatomy of the right ventricle irrespective of its shape. The accuracy and reproducibility of RT3DE in the evaluation of RV global volume and systolic function have been previously validated 6–11 . However, the quantification of RV regional volume and systolic function using RT3DE has not been fully addressed in current literature, 12,13 despite the fact that regional contraction plays an important role in RV global systolic function 14–17 .…”
mentioning
confidence: 99%
“…We should mention that this study did not include the outflow tract in the volume measurement. Gopal et al (2007;Horton et al, 2009;Chua et al, 2009), however, used Tom Tec system to measure the RV volume. 3D full-volume reconstructed surface from four wedges and RV boundary were determined manually to overcome the drop out of the inflow and outflow tract.…”
Section: Rv Volume Measurement Methodsmentioning
confidence: 99%
“…In the meanwhile, tracking the mitral valve together with the ventricle volume was presented by Barcaro et al (2008). ECG signal was used by Zhu et al (2009) to determine the ED and ES frame of the LV in order to generate a dynamic model of the (Gopal et al, 2007;Chua et al, 2009) also used ECG to determine the ED frame through the R wave of the ECG and the ES frame was determined as the smallest cavity area. The biggest and smallest area of the RV cavity were visually tracked in three views; short axis, four chamber and coronal by Ostenfeld et al (2012) to determine the ED and ES cardiac stages.…”
Section: End-diastolic and End-systolic Detectionmentioning
confidence: 99%